Does the high-tech enterprise certification policy promote innovation in China? - Huiling Liu; Xing Fei; Kseniya Yakshtas; Bo Li (Kiel Institute for the World Economy (IfW), 2018)
This study investigates the impacts of Chinese high-tech enterprise certification policy on enterprise innovation by exploiting the unique data of listed companies and their affiliates from 2006 to 2015. The authors exclude firms certified after year 2009 from the sample, because they may have exhibited R&D manipulation. The results show that high-tech enterprise certification can promote Chinese enterprise innovation, especially the innovation captured by invention patents. The results of a rich set of robustness tests all support this conclusion. Regarding the underlying mechanism, high-tech enterprise certification can influence enterprise innovation through tangible and intangible channels. The heterogeneity analysis shows that private enterprises, enterprises in industries with more competition, and equity-inspired enterprises benefit most from high-tech enterprise certification. This paper helps to scientifically evaluate the validity of Chinese innovation policy and contributes to a more comprehensive understanding of enterprise innovation's driving forces as well as the inconclusive relationship between government support and enterprise innovation.
Keywords: O31; O32; O38; 330; high-tech enterprise certification; innovation; R&D manipulation